Effects of Pistacia atlantica resin oil on the level of VEGF, hydroxyproline, antioxidant and wound healing activity in STZ-induced diabetic rats - B. Shahouzehi; M. Shabani; N. Shahrokhi; S. Sadeghiyan; Y. Masoumi-Ardakani (The Ukrainian Biochemical Journal, 2018)
Diabetes mellitus is a chronic metabolic disorder which is followed by many complications. One of these problems following diabetes is diabetic ulcers and 2.5% of diabetic patients develop foot ulcer annually. Natural resources are useful stock for finding traditional treatment. Studies which examined Pistacia atlantica properties showed that it has some beneficial effects including: antimicrobial, antifungal, antioxidant and wound healing. Yet, Pistacia atlantica resin oil effects on diabetic wound have not been examined. Therefore, we evaluate Pistacia atlantica resin oil antioxidant and wound healing activity. Sprague-Dawley male rats were entered to the study and randomly grouped (n = 10) as follows: group 1 – control group – burnt rats which received neither STZ nor Pistacia atlantica resin oil; group 2 – diabetic burnt rats; group 3 – diabetic burnt rats which received 250 µl/day Pistacia atlantica resin oil topically as an ointment for two weeks. At the end of the study antioxidant status, Vascular Endothelial Growth Factor (VEGF) and hydroxyproline contents were examined in the wound area. Our results showed that Pistacia atlantica resin oil has remarkable antioxidant activity in STZ-induced diabetic rats. Also, it promoted VEGF and hydroxyproline contents in the wound area which showed that it increases angiogenesis and collagen turnover in the diabetic wound. We concluded that Pistacia atlantica resin oil can be considered as a new therapeutic agent in diabetic wound healing, and also it is safe, available and cheap treatment of other wounds and skin injuries.